The Linguistic Dimensions of Hadrah Poetry in Shaping the Religious Identity of Students at Dayah Darul Muta’allimin Aceh - Puteri Keumala Sari; Syarifuddin; Zulhelmi; Cut Hanum Salsabila (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to describe the linguistic dimensions of hadrah poetry in shaping the Islamic identity of students at Dayah Darul Muta’allimin Aceh. The research employed a descriptive qualitative method with a case study approach conducted at Dayah Darul Muta’allimin, Aceh Besar. Data were collected through participant observation, in-depth interviews, documentation, and library research. Data analysis utilized the Miles and Huberman model alongside Norman Fairclough’s critical discourse analysis approach. The findings reveal that hadrah poetry functions not only as a form of religious art but also as a linguistic and spiritual medium in constructing students’ religious consciousness. Linguistic analysis identified the use of religious diction such as shalawat, mahabbah, nur, and mahalul qiyam, which represent Islamic ideological values embedded within the Acehnese pesantren tradition. In addition, lexical repetition in phrases such as Ya Rasulullah  was found to strengthen emotional and spiritual effects, while the metaphor of “light” symbolized divine guidance (hidayah) and closeness to Allah SWT. Furthermore, hadrah practices reinforce students’ social solidarity and collective identity through collaborative rehearsals and performances.